COMPARATIVE ANALYSIS OF “KITE RUNNER” AND “A THOUSAND SPLENDID SUNS” BY KHALED HOSSEINI: THEMES, CHARACTERS, AND SOCIOPOLITICAL CONTEXT - Valieva, Nargizakhon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This comparative analysis explores the novels "Kite Runner" and "A Thousand Splendid Suns" by Khaled Hosseini, examining their thematic elements, character development, and sociopolitical context. Through a comprehensive comparative analysis, this article aims to shed light on the similarities and differences between the two novels.